1997
DOI: 10.1002/hep.510250215
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Alcohol Exposure Affects Galactosyltransferase Activity and Glycoconjugates in the Golgi Apparatus of Fetal Rat Hepatocytes

Abstract: been clearly demonstrated in experimental animals, 4,5 in Prenatal exposure to alcohol affects the morphologiwhich important alterations in the ultrastructure of various cal, structural, and functional features of the Golgi appatissues and organs, including the liver, were found to be inratus (GA), thus altering the glycosylation process in feduced by prenatal exposure to ethanol. 6 We have previously tal hepatocytes. To elucidate the cellular mechanisms demonstrated that prenatal exposure to ethanol induces s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…In our studies, the offspring of chronic ethanol-fed mothers showed several hormonal alterations during development (Esquifino et al, 1986;Portolés et al, 1988). Using this animal model, we have reproduced in the rat (Guerri et al, 1984;Sanchis et al, 1986Sanchis et al, , 1987Guerri, 1987;Renau-Piqueras et al, 1997) many alterations observed in children with fetal alcohol syndrome (Clarren and Smith, 1978) who were born of alcoholic mothers.…”
mentioning
confidence: 52%
“…In our studies, the offspring of chronic ethanol-fed mothers showed several hormonal alterations during development (Esquifino et al, 1986;Portolés et al, 1988). Using this animal model, we have reproduced in the rat (Guerri et al, 1984;Sanchis et al, 1986Sanchis et al, , 1987Guerri, 1987;Renau-Piqueras et al, 1997) many alterations observed in children with fetal alcohol syndrome (Clarren and Smith, 1978) who were born of alcoholic mothers.…”
mentioning
confidence: 52%
“…Previous data demonstrate that ethanol-induced changes in the glycoconjugate moieties may easily be due to alterations in the activity of glycosyltranferases and/or glycosidases including galactosyltransferase, sialyltranferase, N-acetylglucosaminyltransferase and sialidase (Guasch et al 1992;Rosenberg and Noble 1994;Renau-Piqueras et al 1997;Ghosh et al 1998;Lakshman et al 1999 II in accordance with the increase in glycoprotein binding to GNA suggesting that alcohol induces an accumulation of N-glycans of high Man and hybrid type sugar chains as well as an alteration in the synthesis of complex oligosaccharides. In fact, the inhibition of Man II results in the synthesis of glycoproteins with glucose-containing high Man structures, or various high-Man or hybrid chains (Hughes and Feeney 1986;Elbein 1991;Herscovics 1999).…”
Section: Ethanol Alters the Glycosylation Molecular Machinerymentioning
confidence: 95%
“…Thus, prenatal alcohol exposure has been reported to induce a striking disorganization of the GA cisternae in about 40% hepatocytes, where the cytochemical activity of several trans-GA markers, including thiamine pyrophosphatase or acid phosphatase, considerably lowered [47]. In addition, these cells displayed a significant reduction in galactosyltransferase activity [48]. Lectin cytochemistry and lectin blotting have also demonstrated that prenatal alcohol exposure results in alterations in the oligosaccharide chain composition of glycoproteins, thus inducing glycoprotein microheterogeneity [44,48].…”
Section: Alcohol Affects Glycosylation and Intracellular Trafficking mentioning
confidence: 99%
“…In addition, these cells displayed a significant reduction in galactosyltransferase activity [48]. Lectin cytochemistry and lectin blotting have also demonstrated that prenatal alcohol exposure results in alterations in the oligosaccharide chain composition of glycoproteins, thus inducing glycoprotein microheterogeneity [44,48]. It is interesting to note that this effect differed in adult and neonatal rat hepatocytes, suggesting that the carbohydrate moiety of some glycoproteins in neonatal hepatocytes differs from that in adult livers [44].…”
Section: Alcohol Affects Glycosylation and Intracellular Trafficking mentioning
confidence: 99%